2021
DOI: 10.1002/btpr.3186
|View full text |Cite
|
Sign up to set email alerts
|

Reshaping cell line development and CMC strategy for fast responses to pandemic outbreak

Abstract: The global pandemic outbreak COVID‐19 (SARS‐COV‐2), has prompted many pharmaceutical companies to develop vaccines and therapeutic biologics for its prevention and treatment. Most of the therapeutic biologics are common human IgG antibodies, which were identified by next‐generation sequencing (NGS) with the B cells from the convalescent patients. To fight against pandemic outbreaks like COVID‐19, biologics development strategies need to be optimized to speed up the timeline. Since the advent of therapeutic bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 44 publications
(89 reference statements)
0
25
0
Order By: Relevance
“… 12 , 13 Just recently, Zhang et al applied the Chemistry, Manufacturing and Controls (CMC) strategies of pool materials for toxicology study by reshaping cell line development within 6 months. 14 We further expedited the development path of JS016, using transient cell lines materials to support IND-enabling toxicology study to shorten the timeline to only a 4-month period. The strategy uses the following: (1) a 200-L bioreactor production scale with transient CHO cell lines to support preclinical, IND-enabling toxicology research, and early CMC development; (2) utilization of mini-pool materials to supply Phase 1 clinical trials; and (3) supply ensuing late-stage and pivotal trial materials with production from established single-clone working cell bank (WCB).…”
Section: Introductionmentioning
confidence: 99%
“… 12 , 13 Just recently, Zhang et al applied the Chemistry, Manufacturing and Controls (CMC) strategies of pool materials for toxicology study by reshaping cell line development within 6 months. 14 We further expedited the development path of JS016, using transient cell lines materials to support IND-enabling toxicology study to shorten the timeline to only a 4-month period. The strategy uses the following: (1) a 200-L bioreactor production scale with transient CHO cell lines to support preclinical, IND-enabling toxicology research, and early CMC development; (2) utilization of mini-pool materials to supply Phase 1 clinical trials; and (3) supply ensuing late-stage and pivotal trial materials with production from established single-clone working cell bank (WCB).…”
Section: Introductionmentioning
confidence: 99%
“…Zhou showed data from a panel of ~12 molecules that demonstrated that non‐clonal pools generated similar product quality to the final selected clones all the way up to the 2000 L production scale. 10 …”
Section: Speedmentioning
confidence: 99%
“…For mAb products, a CMC timeline of 10–12 months from DNA to IND application is already considered expedited. However, during the COVID‐19 emergency, combined efforts from sponsors, contract development and manufacturing organizations (CDMO), and regulatory agencies have drastically shortened CMC timelines from DNA to IND to 3–6 months (Figure 1 ), and from DNA to EUA to less than 2 years, for a number of SARS‐CoV‐2 neutralizing antibodies (Agostinetto et al, 2022 ; Kelley, 2020 ; McGovern et al, 2022 ; G. Xu et al, 2022 ; Zhang et al, 2021 ). As CLD serves as the initiation point for the entire CMC program and provides the final clone intended for manufacturing, effective management of CLD timeline and product quality is of utmost importance to ensure the timely delivery of high‐quality clinical materials.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous paper, we outlined a series of important steps to accelerate the overall CMC timeline in response to COVID‐19 emergency from the perspective of CLD (Zhang et al, 2021 ). Four major designs are described.…”
Section: Introductionmentioning
confidence: 99%